2019
DOI: 10.17584/rcch.2019v13i1.8018
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance and gaseous exchanges of the radish under saline stress and ascorbic acid application

Abstract: The radish is a short-cycle vegetable that has excellent nutritional and medicinal properties. It is considered rustic, meaning it tolerates adverse conditions with the possibility of being irrigated with saline water, which creates stress. In this context, this study aimed to evaluate the effect of electrical conductivities in irrigation water and doses of ascorbic acid on the agronomic performance and gaseous exchanges of radishes. This experiment was carried out in a protected environment at the Agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…However, we found that 2 mM AA did not attenuate stress caused by either a water excess (W100) or a de cit (W50). These ndings were similar to those of radish plants grown under saline, where AA also did not attenuate stress effects(Basílio et al 2018;Leal et al 2019).…”
supporting
confidence: 80%
“…However, we found that 2 mM AA did not attenuate stress caused by either a water excess (W100) or a de cit (W50). These ndings were similar to those of radish plants grown under saline, where AA also did not attenuate stress effects(Basílio et al 2018;Leal et al 2019).…”
supporting
confidence: 80%